Experts contributions to the development of a non-sugar sweeteners warning label for Brazilian food products - Mariana Ribeiro; Priscila de Morais Sato; Carlos Felipe Urquizar Rojas; Carla Galvão Spinillo; Laís Amaral Mais; Camila Aparecida Borges; Ana Paula Bortoletto Martins (PLoS ONE, 2025)
The consumption of non-sugar sweeteners (NSS) has been associated with potential health risks, including glucose intolerance, alterations in the intestinal microbiota which lead to metabolic abnormalities including pancreatic endocrine dysfunction, aggravation of kidney disease, increased risk of cancer and adverse cardiovascular outcomes. In Brazil, the presence of NSS in ultra-processed food products (UPFP) is only reported in ingredient lists, which Brazilian consumers struggle to locate and understand. On the other hand, countries such as Argentina and Mexico have implemented a cautionary legend for NSS in packaged foods and beverages. This study aimed to evaluate expert opinion on the design attributes of NSS warning labels intended to inform consumers about the presence of these sweeteners in packaged foods and beverages sold in Brazil. For this purpose, a panel of experts was conducted to discuss, judge and decide on the technical aspects of readability, visibility, attention, perceived healthiness and health risk of the proposed warning labels for NSS in packaged foods and beverages in Brazil. Based on the specific attributes, the experts identified two NSS warning messages as the most suitable: ‘Attention: contains non-sugar sweetener — not recommended for children and for weight control’ and ‘Attention: contains non-sugar sweetener’. According to the experts, these messages should be displayed as front-of-package warnings in black rectangular boxes with white text, beginning with the signal word ‘Attention’ and positioned on the main panel near the Brazilian front-of-package nutrition labeling. The study provides interdisciplinary evidence and expert insight, to support the development of NSS warning labels in Brazil.